Study Of Prevalence of Fluorosis in Endemic Village of Kankar District of Chhattisgarh State, India - Gitte, Sunil V; Kamble, K M; Sabat, Ramanath N (National Journal of Community Medicine, 2014)
Background: Endemic fluorosis is an important public health problem in certain pockets of Chhattisgarh. Fluorosis is caused by exposure to a continuous high level of fluoride for a long time leads to dental and skeletal deformities. Objectives: Objective of the study is to find out the prevalence of dental and skeletal fluorosis among the population and to assess its relation to the drinking water fluoride level. Methods: Cross sectional survey was undertaken in Domarpali Village, of the Kanker district, of Chhattisgarh state in May 2013. The survey covered 1359 (85%) individuals, including 824 males and 769 females. The prevalence of dental and skeletal fluorosis was assessed by clinical examination of individuals undertaken by house to house visits. Water fluoride levels of drinking water sources were determined. Results: The prevalence of dental fluorosis was 24.8 % and skeletal fluorosis was 6.0%. Both the types were more common in males. Dental fluorosis was higher in the age group of 13 to19 years. The prevalence of skeletal fluorosis increased with increasing age. Common skeletal deformities were genu varum (12.2%) and genu valgum (0.7 %). Water fluoride levels in different localities ranged from 0.5 to 2.8 ppm. Conclusions: This study has shown the relation of fluorosis to high fluoride levels of prime water sources. Change in water source from deep tube well and a hand pump with health education to the community is needed to reduce in order to reduce the problem.